Strategi Marketing dalam Optimalisasi Minat Pengunjung Website caribakatmu.com dengan Pendekatan Technology Acceptance Model - Tonny Yuwanda; Abdi Fadhlan; Mayang Bundo; Omia Crefioza (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to contribute as a marketing strategy and increase visitors to the caribakatmu.com website, which was managed by PT Ahad Edutama Inovasi with the technology acceptance model (TAM) approach. This service method was Participatory Action Research (PAR), where the service team assisted partners in research to solve problems. Data was collected by distributing questionnaires to 100 website user respondents in which the questions were based on the approach used. Path analysis was used in this activity with the SEM-PLS program to comprehensively determine the direct and indirect effects of exogenous variables on endogenous ones. This service analysis showed that Caribakatmu.com was following the technology acceptance model. The variables perceived ease of use and perceived usefulness significantly affect attitude towards using and behavioral intention. However, with the addition of age and gender control variables, there are several suggestions for Caribakatmu.com, including 1) the Development of services for the student level up to the company level; 2) Expanding personality testing by providing visual tests, memory games and creativity so that talent mapping is comprehensive; 3) Adding the share feature so that users can promote this website.